Mechanistic-empirical pavement design guide: features and distinctive elements - Martínez Díaz, Margarita; Pérez, Ignacio (Revista de la Construcción. Journal of Construction, 2015)
This paper is aimed at describing the most distinctive features of the pavement design method known as Mechanistic-Empirical Pavement Design Guide and to compare it with other renowned methodologies, while emphasizing its advantages and disadvantages. The MEPDG can accurately predict damage evolution, thus helping to choose the most appropriate design for new pavements or to schedule the conservation of the already existing ones. After analyzing different pavement design and management methods, the MEPDG stands out as the most comprehensive one as it takes into account and properly combines the greatest number of factors that affect the pavement. Therefore, some countries outside the USA have already imported and calibrated this method, what, at the same time, allows the scientific community to carry out comparative studies and improve its small deficiencies.